2020
DOI: 10.3390/min10100870
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Analysis of α-Quartz Crystals Subjected to Shear Stress

Abstract: This study assesses the correlations between the intensity of stress undergone by crystals and the morphological characteristics of particles and fracturing products. The effects of the fractures on the microstructure of quartz are also studied. Alpha quartz, subjected to shear stress, is quickly crushed according to a fracturing sequence, with a total fracture length that is correlated to the stress rate. The shear stress generates a sequence of macro and microstructural events, in particular localized meltin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Wilk et al [6] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa. Laboratory shock experiments by Martinelli et al [79] used quartz crystals with a minimum diameter of 3400 µm, larger than we tested. The reported compression applied was as low as 0.2 GPa; the maximum compression applied is unclear but appears to have been <1 GPa.…”
Section: Previous Studies Of Amorphous Silica In Quartz Grainsmentioning
confidence: 99%
“…Wilk et al [6] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa. Laboratory shock experiments by Martinelli et al [79] used quartz crystals with a minimum diameter of 3400 µm, larger than we tested. The reported compression applied was as low as 0.2 GPa; the maximum compression applied is unclear but appears to have been <1 GPa.…”
Section: Previous Studies Of Amorphous Silica In Quartz Grainsmentioning
confidence: 99%
“…Laboratory shock experiments by Martinelli et al [90] produced intragranular fractures in quartz crystals with a minimum diameter of 3400 µm, larger than any we examined. The fracturing process reportedly produced amorphous silica composed of low-temperature nanocrystalline cristobalite, which was not observed in the fractures of our study.…”
mentioning
confidence: 63%
“…In laboratory experiments, Martinelli et al [90] concluded that fractures in quartz form rapidly in <50 ns not by compression but by tensional expansion produced by the reflected shockwave. They found that the fracturing process generates temperatures >1713°C, the melting point of quartz, thus producing amorphous silica along the fractures, as first proposed by Ernstson [33].…”
Section: Potential Formation Mechanismsmentioning
confidence: 99%